(3QLGd GdTjNs - (3GdWhSj, CHh LYaQ, fUjQ GdOjf, eMeO Hf eMeO Hf GdMSf, J (B672 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B... (3aEfj bO CLHJ Edi eG JcQQ GdTjN GdaGVd ajg ef LejY cJGH jTJed Ydi CSeGA GdQLGd GdPjf Qhh Yf GdfHj Udi Gddg Ydjg hSde hBdg hYf GdCFeI (B...s
(3BNQgG (B:s
... (3RcGQ Hf eGdc Gdchaj CHh YHO Gddg Hf GdMGQS Hf SdeI GdgePGfj ehdGge chaj (B, (3RgjQ Hf (B... (3CHh NKeI GdLYaj , RgjQ Hf eMeO GdNQSGfj , CHh GdefPQ Scf ecI (B..s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, ddRQcdj (B7/ 30s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
Keywords: (3GdMOjK hGdeUWdMs